STUDYING THE EFFECT OF SOLAR ACTIVITIES ON THUNDERSTORMS IN IRAQ FOR SOLAR-CYCLES 23 & 24 - Ramadan, Mohammed; Hussain, Imad (Malaysian Journal of Science, 2022)
Studying the impact of solar activity on the Earth’s climate is significant for predicting the change of its elements for long periods. Most studies have focused on the relationship between sunspots and changes in one of the climate elements. In this research, the effect of the solar activities that consist of coronal mass ejections and solar flare, and the sunspots number on thunderstorms that occur during the winter season in Iraq for the period from (1996-2019) representing the Solar-Cycles 23 & 24, respectively, were investigated in this study. In general, the statistical results show that, the monthly average increase for each of the following: energies of coronal mass ejections, solar flares, and the sunspots number, the monthly frequency of thunderstorms decreases. The Solar-Cycle 24 is the weakest among the cycles of the last century; therefore, its results were not precise.